Dayamihan adoption of bioenergy and carbon capture storage through a biorefinery and agriculture hub - Pangilinan, Basilio A. (College of Architecture, University of the Philippines Diliman, 2023)
As the world continues to recover from the Covid-19 pandemic; carbon dioxide in the atmosphere is reverting back to pre-pandemic levels and worsening our climate change problem. A major contributor to greenhouse gas (GHG) emissions is agriculture. The sector accounts for 18.5% of global GHG emissions, largely attributed to agricultural waste and harmful production practices. Scholars argue that the mitigation of animal agriculture can eliminate the majority of the GHG emission from the sector. However, this drastic change is not compatible with the current lifestyles across the globe. Incremental improvement in agricultural processes and waste recycling through the use of proven technology can offer a more suitable solution. Such technology is Bioenergy and Carbon Capture Storage (BECCS) which utilizes large amounts of crop and animal by-product, collectively known as biomass, to create energy and higher value products. This prevents biomass from being openly burned or decomposed, releasing GHG to the atmosphere. In the Philippines, an estimated 95% of rice crop waste is burned in open-fit fires that negatively impact the environment. This comprehensive design project explores the factors incentivising harmful practices such as crop burning and the attitudes towards new agricultural technology by farmers through interviews and discussions. Using information from farmers, experts and researchers, this project addresses the adoption of BECCS with the design of a biorefinery and Agriculture Hub in Calauan, Laguna. Having a dedicated space for research on the technology to suit local use. Furthermore, by making the technology more accessible, small-holder farmers are able to reap the economic benefits of BECCS. This project alone will not reverse our climate crisis, but will contribute to a systematic solution that can bring a brighter future for farmers and environment.